Radiation Exposure and Image Quality in X-Ray Diagnostic Radiology Physical Principles and Clinical Applications - Aichinger, Horst; Dierker, Joachim; Joite-Barfuß, Sigrid; Säbel, Manfred (Springer Berlin Heidelberg : Imprint: Springer, 2012)
Diagnostic X-rays are the largest contributor to radiation exposure to the general population, and protecting the patient from radiation damage is a major aim of modern health policy. Once the decision has been taken to use ionising radiation for imaging in a particular patient, it is necessary to optimize the image acquisition process taking into account the diagnostic quality of the images and the radiation dose to the patient. Both image quality and radiation dose are affected by a number of parameters, knowledge of which permits scientifically based decision making. The authors of this second edition of Radiation Exposure and Image Quality in X-ray Diagnostic Radiology have spent many years studying the optimization of radiological imaging. In this book they present in detail the basic physical principles of diagnostic radiology and their application to clinical problems. Particular attention is devoted to evaluation of the dose to the patient, the influence of scattered radiation on image quality, the use of antiscatter grids, and optimization of image quality and dose. The final section is a supplement containing tables of data and graphical depictions of X-ray spectra, interaction coefficients, characteristics of X-ray beams, and other aspects relevant to patient dose calculations. In addition, a complementary CD-ROM contains a user-friendly Excel file database covering these aspects that can be used in the reader's own programs. Since the first edition, the text, figures, tables, and references have all been thoroughly updated, and more detailed attention is now paid to image quality and radiation exposure when using digital imaging and computed tomography. This book will be an invaluable aid to medical physicists when performing calculations relating to patient dose and image quality, and will also prove useful for diagnostic radiologists and engineers.